1975
DOI: 10.1104/pp.55.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Anthocyanin Synthesis

Abstract: (8-10, 15, 17, 18, 24, 27, 35, 36, 39, 40, 44). One is the low energy, R -FR' reversible phytochrome system (1, 8,12,15,17,18,28,40,44) and the other is the high energy reaction, also called high irradiance reaction system of plant photomorphogenesis (4,9,10,14,15,28,44 (4,14,28,29,37,41,44 germination (11, 14, 22, 23, 42, 45).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
2

Year Published

1976
1976
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(59 citation statements)
references
References 35 publications
2
47
2
Order By: Relevance
“…The results reported in this note and in previous ones (11,19) show that STM and CAP inhibit the development of the photosynthetic apparatus and strongly enhance anthocyanin synthesis in young seedlings. The cause for the enhancement of anthocyanin production has not been established; it has been suggested (19) that the inhibition of the development of the photosynthetic apparatus may result in an increase of the pool size of one or more compounds needed for anthocyanin synthesis; this suggestion is supported, but not proven, by the results shown in Figure 3.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The results reported in this note and in previous ones (11,19) show that STM and CAP inhibit the development of the photosynthetic apparatus and strongly enhance anthocyanin synthesis in young seedlings. The cause for the enhancement of anthocyanin production has not been established; it has been suggested (19) that the inhibition of the development of the photosynthetic apparatus may result in an increase of the pool size of one or more compounds needed for anthocyanin synthesis; this suggestion is supported, but not proven, by the results shown in Figure 3.…”
Section: Discussionsupporting
confidence: 54%
“…Photosynthesis may play a role in the HIR anthocyanin synthesis of young, dark-grown seedlings exposed to continuous FR irradiation (13,14). However, the latter suggestion is not supported by results obtained in various laboratories, including our own (5,(10)(11)(12)19). The results submitted in this paper confirm and extend previous observations (11).…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…The anthocyanin content was calculated according to Mancinelli et al (1975) and reported as mg mL -1 g FW -1…”
Section: Methodsmentioning
confidence: 99%